CFD-Based Determination of the Optimal Blowing and Suction Air Volume Ratio of Dual-Radial Swirl Shielding Ventilation in a Fully Mechanized Excavation Face. (17th September 2021) - Wu, Kuan; Shi, Shiliang; Shi, Yijie; Chen, Yong
Abstract : Dust is one of the main pollutants in coal mines, which seriously affects the physical and mental health of workers, as well as the safe production in underground mines. Dual-radial swirl shielding ventilation is a new ventilation method for a fully mechanized excavation face and can effectively reduce the dust concentration in the underground. The dust control effect of dual-radial swirl shielding ventilation is mainly affected by the thickness and integrity of the shielding air curtain, as well as the disturbance of the flow field near the air curtain. By changing the blowing and suction air volume ratio of the air duct, the strength of the radial air curtain can be improved, and the dust control effect of the dual-radial swirl shielding ventilation system can be effectively improved. In order to determine the optimal operating parameters of the dual-radial swirl shielding ventilation system, a numerical simulation method was used to conduct an in-depth study on the blowing and suction air volume ratio of the system. The results showed that when the blowing and suction air volume ratio of the air duct was 1.5, the radial air curtain had the highest strength. Under this condition, the dust concentration at the driver's position of the roadheader was the lowest, and the dual-radial swirl shielding ventilation system can achieve an ideal dust control effect.